Clinical characteristics and changing trajectories of esophageal cancer and gastric cancer in China from 2010 to 2019: An analysis of a hospital-based database of 24,327 patients - Wang, Qiang; Zhang, Xiaorui; Zhong, Yuxin; Wei, Shijing; Li, Li; Wei, Wenqiang; Liu, Fen; Li, Yong; Wang, Shaoming (Frontiers in Oncology, 2023)
Purpose This analysis aimed to investigate the clinical characteristics and changing trajectories of gastric cancer (GC) and esophageal cancer (EC). Methods We collected data from a large cancer hospital in Beijing, China, from 2010 to 2019. Joinpoint regression was used to analyze the trends of histological characteristics and comorbidities. Results From 2010 to 2019, there were a total of 10,083 EC patients and 14,244 GC patients. Patients were mainly men and diagnosed at 55-64 years old. Metabolic comorbidity was the most common comorbidity, with hypertension being predominant. The percentages of stage I showed significant increases for EC [average annual percent change (AAPC): 10.5%] and GC (AAPC: 9.7%) patients. We also observed an increasing trend of EC and GC patients over 65 years old. For EC patients, esophageal squamous cell carcinoma (93.1%) remained as the prioritized subtype, and the middle third of the esophagus was the most common site. EC patients with three or more comorbidities increased from 0.1% to 2.2% (AAPC, 27.7%; 95% CI, 14.7% to 42.2%). For GC patients, adenocarcinoma accounts for 86.9% of the total cases, and cardia was the most common site. The ulcerative comorbidity rate decreased from 2.0% to 1.2% (AAPC, −6.1%; 95% CI, −11.6% to −0.3%). Conclusion ESCC remained as the prioritized histological subtype, and the middle third of the esophagus was the most common site of EC. The majority of GC patients had adenocarcinoma, and the cardia was the most common site. There was an increasing trend of patients diagnosed at stage I. These findings provide scientific evidence to guide future treatment.